Genome-wide association studies identify susceptibility loci for epithelial ovarian cancer in east Asian women - Lawrenson, Kate; Song, Fengju; Hazelett, Dennis J.; Kar, Siddhartha P.; Tyrer, Jonathan; Phelan, Catherine M.; Corona, Rosario I.; Rodríguez-Malavé, Norma I.; Seo, Ji-Hei; Adler, Emily; Coetzee, Simon G.; Segato, Felipe; et al. (Gynecologic oncology, 2019)
Genome-wide association studies (GWASs) for epithelial ovarian cancer (EOC) have focused largely on populations of European ancestry. We aimed to identify common germline variants associated with EOC risk in Asian women. Genotyping was performed as part of the OncoArray project. Samples with >60% Asian ancestry were included in the analysis. Genotyping was performed on 533,631 SNPs in 3238 Asian subjects diagnosed with invasive or borderline EOC and 4083 unaffected controls. After imputation, genotypes were available for 11,595,112 SNPs to identify associations. At chromosome 6p25.2, SNP rs7748275 was associated with risk of serous EOC (odds ratio [OR] = 1.34, P = 8.7 × 10−9) and high-grade serous EOC (HGSOC) (OR = 1.34, P = 4.3 × 10−9). SNP rs6902488 at 6p25.2 (r2 = 0.97 with rs7748275) lies in an active enhancer and is predicted to impact binding of STAT3, P300 and ELF1. We identified additional risk loci with low Bayesian false discovery probability (BFDP) scores, indicating they are likely to be true risk associations (BFDP <10%). At chromosome 20q11.22, rs74272064 was associated with HGSOC risk (OR = 1.27, P = 9.0 × 10−8). Overall EOC risk was associated with rs10260419 at chromosome 7p21.3 (OR = 1.33, P = 1.2 × 10−7) and rs74917072 at chromosome 2q37.3 (OR = 1.25, P = 4.7 × 10−7). At 2q37.3, expression quantitative trait locus analysis in 404 HGSOC tissues identified ESPNL as a putative candidate susceptibility gene (P = 1.2 × 10−7). While some risk loci were shared between East Asian and European populations, others were population-specific, indicating that the landscape of EOC risk in Asian women has both shared and unique features compared to women of European ancestry. •This study analyzed genotyping data from >7,000 individuals of Asian descent to find risk loci for epithelial ovarian cancer•We identified two novel genome-wide significant loci, plus evidence of association at an additional 28 regions•eQTL analyses in 404 TCGA tumors highlight ESPNL as a novel susceptibility gene for ovarian cancer